Performance Evaluation Systems as a Management Control Mechanism: Its Impact on Trust and Job Performance - Neny Desriani; Yuliansyah Yuliansyah; Einde Evana (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to examine performance evaluation systems as a management control mechanism in shaping subordinates’ trust in their supervisors and examining its impact on job performance. Research Methodology: This study employs a survey-based approach using data collected from 103 teachers in private educational institutions in Indonesia. Data were obtained through structured questionnaires adapted from prior studies. Both measurement and structural models were examined using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0 software. Results: This study shows how performance evaluation systems can be used as a management control mechanism to improve work performance and build trust. The findings emphasize how crucial it is for organizational settings to have transparent and organized evaluation procedures. Conclusions: This study demonstrates that performance evaluation systems function as an effective management control mechanism in fostering trust and improving job performance. The results highlight the importance of structured and transparent evaluation processes in organizational settings. Limitations: This study's narrow focus on a particular institutional setting and small sample size may restrict how broadly the results may be applied. Contributions: This study contributes extends to the body of literature in management accounting by presenting actual data regarding the behavioral function of evaluation systems. It highlights trust as a key mechanism linking control practices to performance outcomes, offering practical insights for organizations in designing transparent evaluation systems.